Tribological effects of nano-based engine oil diluted with biodiesel fuel - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; tamaldin, noreffendy; Mat Nuri, Nur Rashid (Inderscience, 2017)
The aim of this study was to investigate the tribological effects of nano-based engine oil diluted with biodiesel fuel. The nano-oil was prepared by disperse an optimal composition 0.5 vol.% of 70 nm hexagonal boron nitride (hBN) nanoparticles in diesel engine oil using sonication technique. Sample was diluted by difference percentages of B100 biodiesel fuel in range of 5-20 vol.%. The tribological test was performed using a four-ball tribometer. It was found that the addition of biodiesel fuel increases the coefficient of friction (COF) and seizure wears as compared with nano-oil. However, there is no significant effect on the extreme pressure (EP) properties, where the seizure for all tested samples starts to occur at 981 N.